Meningkatkan Hasil Belajar Siswa di SD Negeri Tanjungsari dengan Model Experiential Learning - ‘Aini, Shinta Futichatul (Prosiding University Research Colloquium, 2021)
The purpose of this study was to find out how the effect of using the Experiential Learning model as a means to improve student learning outcomes at Tanjungsari Elementary School during the Covid-19 pandemic. This research uses Classroom Action Research (CAR) with a quantitative approach. The subjects in this study were the 5th grade students of SD N Tanjungsari, totaling 22 children. However, the author only took a sample of 5 children due to the current pandemic situation which did not allow the author to collect all children in one class. The author uses an essay test to measure students’ abilities. The average score of Cycle 1 obtained by students is 71 and the average score of Cycle 2 obtained by students is 82. It can be seen that there is a significant increase in scores after and before conducting research using the Experiential Learning model. The results of this study indicate that the Experiential Learning model has a positive effect on increasing student learning outcomes.